The Mahakal Temple comprises of Mahakal and Baijnath temples - Temples of India Project Team (Jio Institute, 2024)
The Mahakal Temple comprises twin structures referred to as Mahakal and Baijnath. Dedicated to Lord Shiva, this temple features Shivalingas in both sanctuaries. Facing west, the Mahakal Temple consists of a mukhamandapa, mandapa, antarala, and a garbhagriha in the southern direction, along with another garbhagriha in the eastern direction.